Pengaruh Perbedaan Jenis Pakan terhadap Pertumbuhan Populasi Brachionus plicatilis - Regina Melianawati; Adi Hanafi; Made Suastika (Jurnal Perikanan Universitas Gadjah Mada, 2006)
The objective of this research was to know the effect of different feed on the growth of rotifer, Brachionus plicatilis population. Three combinations of feed namely (A) yeast + enrichment ingredient; (B) Isochrysis tahiti + yeast + enrichment ingredient and (C) Isochrysis tahiti were used as treatments in triplicates. Initial density of B. plicatilis was 100 ind./ml. Feeding frequency was twice per day, at 08:00 am and 16:00 pm. This experiment was carried out for 72 hours, and sampling was done every 24 hours. The results showed that the highest density for treatment A, B and C were 330.3±7.6, 305.0±63.8, and 300.0±10.0 ind./ml, respectively. In addition, the highest population reached at 660,667, 610,000 and 600,000 individuals for treatments A, B, and C, respectively. Percentages of B. plicatilis with eggs in each population were 15.14, 20.46, and 13.95% for treatments A, B, and C, respectively. These results indicated that yeast and enrichment ingredient gave the highest growth of Brachionus plicatilis population.